JUVENILE ARTHRITIS IN PEDIATRIC AND ADULT RHEUMATOLOGY SERVICE: THE PROBLEM OF CONTINUITY IN THE MANAGEMENT OF PATIENTS - I. P. Nikishina; O. M. Kostareva (Научно-практическая ревматология, 2018)
The undeniable progress made over the last decade in the treatment of patients with severe juvenile arthritis has ranked in the order of priorities for the provision of efficient and reliable continuity in the management tactics for patients after their transition from their follow-up by a pediatrician to adult rheumatology service. A number of objective difficulties in organizing such continuity are associated primarily with the heterogeneity of the juvenile arthritis group in its clinical manifestations and nosological outcomes. The features of physiological processes of a growing organism cause significant differences in the nature of the course, manifestations of certain clinically significant syndromes (for example, delayed axial skeleton involvement after the onset in juvenile spondyloarthritis), radiological pattern and immunological markers in juvenile-onset rheumatic diseases. Timely active therapy with increasingly available innovative technologies, biological agents in particular, provides a successful disease-modifying effect, so when a patient with juvenile arthritis is transferred from his/her follow-up by a pediatrician to adult rheumatology service, there may be a wrong opinion about the performed redundant therapy and the expediency of its cancellation or correction, which sometimes leads to irreparable negative consequences. The used indices and other tools to assess the activity and functional status are fundamentally different in children and adults with joint inflammatory diseases. The paper presents a brief review of the current state of the problem and international experience with continuity in the follow-up of patients with juvenile arthritis between pediatric and adult rheumatology service.